Use of magnetic field calculation tools to design MV/LV substations - Wall, Carlos Alberto (2015)
Medium Voltage (MV) to Low Voltage (LV) Substations are one of the last links in the distribution process of Electric Power. Associated with these is the generation of magnetic field. These have generated great concern in the population due to its possible link to health effects in humans, so it is necessary to know what are the levels generated by existing and new facilities, considering different constructive topologies. To achieve the objective, magnetic field calculations are performed using 3D simulation tools, allowing to reproduce the layout of ground level substations, knowing the magnetic field values for different loading conditions and considering balanced and unbalanced load conditions, with current in neutral conductors. In 2013 measurement campaigns of Magnetic Field on substations were performed, also loads were surveyed. The results of the calculation of magnetic field generated by ground level substations, considering different topologies used in Argentina are presented in this paper. In order to validate the results, comparisons between measured and calculated values are performed. Generated levels are studied for different cases. Obtained magnetic fields values are compared with limits of Argentinean regulation and recommended references values by international organizations such as ICNIRP (International Commission on Non-Ionizing Radiation Protection) and IEEE (Institute of Electrical and Electronics Engineers).